Case Report: Two Cases of Subacute Thyroiditis Following SARS-CoV-2 Vaccination - Bornemann, Catherine; Woyk, Katharina; Bouter, Caroline (Frontiers in Medicine, 2021)
Subacute thyroiditis is an inflammatory thyroid disorder associated with viral infections. Rare cases of subacute thyroiditis have also been described following vaccination. Recently, a few cases of subacute thyroiditis following SARS-CoV-2 vaccination have also been reported. Here, we present two cases of cytological proven subacute thyroiditis after receiving the first dose of a SARS-CoV-2 vaccination. We describe clinical, laboratory, imaging, and cytological findings in two cases of subacute thyroiditis that presented in our department two weeks after SARS-CoV-2 vaccination with Spikevax (Moderna Biotech, Spain) and Vaxzevria (AstraZeneca; Sweden). Both cases did not have a previous history of thyroid disorders and presented with anterior and lateral neck pain. Clinical test results, as well as cytological findings, were consistent with subacute thyroiditis. Subacute thyroiditis may develop following a SARS-CoV-2 vaccination and should be considered as a possible side effect in cases that present with thyroid pain.